Bhayangkara Lemdiklat Polri Hospital Strategy in Implementing The Standard Inpatient Class of the National Health Insurance (Kris JKN) - Siti Masithoh; Alih Germas Kodyat; Atik Kridawati (Green Publisher Indonesia, 2025)
The Government Regulation No. 59 of 2024, has mandated the implementation of the Standard Inpatient Class (KRIS) policy as a major reform within the National Health Insurance (JKN) system. This policy aims to eliminate disparities in inpatient healthcare services by ensuring equal access and quality of care for all BPJS participants, regardless of their premium contribution levels. This study analyzes the readiness of Bhayangkara Lemdiklat POLRI Hospital to implement the KRIS policy and formulates suitable strategies based on SWOT analysis. A qualitative research design was employed, utilizing observation, document review, and regulatory analysis as data collection techniques. The results show that the hospital has reached a high level of preparedness, with 98.61% of its patients being JKN participants, predominantly elderly and female. The hospital has met the majority of requirements across the four main KRIS implementation pillars: work planning, infrastructure readiness, asset management, and operational execution. However, two physical indicators—ventilation (97.65%) and room temperature (98.07%)—have yet to meet full compliance. The IFE and EFE scores of 3.06 and 3.00, respectively, place the hospital in Quadrant I of the IE Matrix, indicating a strategic position for aggressive growth. Accordingly, a Strength–Opportunity (SO) strategy is recommended, leveraging the hospital's internal strengths to capitalize on external opportunities and ensure that the implementation of KRIS is carried out effectively, efficiently, and sustainably.